Demographic transition and ageing in Latin America and the Caribbean: social and bioethical facts and comments. - Agar Corbinos, Lorenzo (Acta Bioethica, 2001)
At the beginning of the 19th century, the estimated world population was 978 millions. In more developed regions the proportion of people older than 60 was around 20%. Population in Latin America and the Caribbean will grow approximately 180 millions within 2000 and 2025. More than one third of that growth will correspond to old age people. In Latin America and the Caribbean the reality associated with the state of demographic transition is very diversified, which has social, ethical, and economical implications according to the different countries in the Region. The transformation of the structure by ages results in particular social, economic, and political demands. At the same time the social-demographic differences, particularly the age structure, emphasize the difference in the treatment of bioethical issues. Ageing appears in the more advanced transitional countries of the Region, as a linked phenomenon, on the one hand by the increasing proportion of senior citizens, and on the other, by the improved quality of life in the old age years. Bioethical issues will gain greater importance not only because of the increased number and proportion of senior citizens, but also education will place on a more distinguished level the social requirements for autonomy, a dignified treatment, and a greater participation in patient-doctor relationship, diagnostics and treatments. Bioethical considerations, particularlythose principles closest to social sciences as justice, equality and autonomy, tend to gain greater importance in situations concerning the abrupt growth of senior citizen population.